Occurrence of Salmonella in the Cattle Production in France - Laetitia Bonifait; Amandine Thépault; Louise Baugé; Sandra Rouxel; Françoise Le Gall; Marianne Chemaly (Microorganisms, 2021)
Salmonella is among the most common foodborne pathogens worldwide, and can lead to acute gastroenteritis. Along with poultry, cattle production is recognized as an important source of human infection. Salmonella transmission from cattle to humans can occur through the environment, or through close contact with sick animals or their derived products. This study aimed to investigate the intestinal carriage of Salmonella spp. within French cattle production. A total of 959 cattle intestinal samples, from one of the largest French slaughterhouses, were analyzed. Isolated strains were genotyped by pulsed field gel electrophoresis (PFGE), and a sub-selection was taken by whole genome sequencing (WGS). Twenty-nine samples were positive for Salmonella spp., yielding an estimated prevalence of 3% in cattle production. Eight different Salmonella serotypes were found: Montevideo was the most prevalent (34%), followed by Mbandaka (24%) and Anatum (14%). PFGE genotyping allowed the clustering of Salmonella isolates according to their serotype. Within the clusters, some isolates presented 100% similarity. To investigate potential epidemiological links between them, WGS and core genome multilocus sequence typing (cgMLST) were used, revealing identical profiles between isolates originating from different areas and/or different animal breeds. This investigation provides new insights on Salmonella serotype epidemiology in cattle production in France.